An Interdisciplinary Approach To Promoting Digital Learning Innovation - Maya Kusumawati; Rendi Pratama (CV JK Riset Publishing Group, 2025)
This study aims to analyze the role of an interdisciplinary approach in fostering digital learning innovation in 21st-century education. The interdisciplinary approach is considered relevant as it enables the integration of knowledge across disciplines, allowing students to gain more contextual, critical, and creative learning experiences. The research employed a descriptive qualitative method by examining digital learning practices in several educational institutions. The findings reveal that interdisciplinary integration enhances students' critical thinking, creativity, and collaboration skills. Moreover, the use of project-based digital media strengthens social competencies such as communication and teamwork. Nevertheless, the study also identified several challenges, including limited digital literacy among teachers, inadequate infrastructure, and the need for stronger stakeholder collaboration. These findings highlight the importance of continuous teacher training, inclusive educational policies, and sufficient technological support. Thus, the interdisciplinary approach serves not only as an innovative strategy for digital learning but also as a foundation for establishing a sustainable and adaptive educational ecosystem in response to global changes.